2015
DOI: 10.5194/acpd-15-30409-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In situ secondary organic aerosol formation from ambient pine forest air using an oxidation flow reactor

Abstract: Abstract. Ambient air was oxidized by OH radicals in an oxidation flow reactor (OFR) located in a montane pine forest during the BEACHON-RoMBAS campaign to study biogenic secondary organic aerosol (SOA) formation and aging. High OH concentrations and short residence times allowed for semi-continuous cycling through a large range of OH exposures ranging from hours to weeks of equivalent (eq.) atmospheric aging. A simple model is derived and used to account for the relative time scales of condensation of low vol… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(70 citation statements)
references
References 99 publications
2
67
1
Order By: Relevance
“…This trend may be due to the transition of functionalization reactions to fragmentation ones (Kroll et al, 2009;Lambe et al, 2011a). Previous oxidation flow reactor studies suggest that gas-phase chemistry dominates over heterogeneous OH oxidation at OH levels below 1.0 × 10 12 molecules cm −3 s Palm et al, 2016). In this study, the highest OH exposure was 5.28 × 10 11 molecules cm −3 s, and heterogeneous oxidation of SOA may not play an important role in reducing the mass of SOA, although we cannot exclude that it plays a role.…”
Section: Estimation Of Alw Contentcontrasting
confidence: 55%
“…This trend may be due to the transition of functionalization reactions to fragmentation ones (Kroll et al, 2009;Lambe et al, 2011a). Previous oxidation flow reactor studies suggest that gas-phase chemistry dominates over heterogeneous OH oxidation at OH levels below 1.0 × 10 12 molecules cm −3 s Palm et al, 2016). In this study, the highest OH exposure was 5.28 × 10 11 molecules cm −3 s, and heterogeneous oxidation of SOA may not play an important role in reducing the mass of SOA, although we cannot exclude that it plays a role.…”
Section: Estimation Of Alw Contentcontrasting
confidence: 55%
“…This correction is thus applied in order to relate the OFR measurements to what would occur in the atmosphere. This model was verified using sulfate aerosol formation from SO2 during this study 11 . The average overall correction factor is 1.8x.…”
Section: Soa Formation Measurementmentioning
confidence: 58%
“…A detailed description of the OFR measurements during this field study can be found in Palm et al 11 ; a brief summary is presented here. In situ SOA formation was measured by the AMS and a (similar to chamber wall losses) 16 , being oxidized again prior to condensation leading to volatile fragmentation products, or exiting the OFR to condense rapidly on sampling line walls.…”
Section: Soa Formation Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the reduction of SCI based oligomers is the major reason for the decrease in SOA yields from isoprene-NO 2 photooxidations. It is noted that the wall loss of semi-volatile organic compounds (SVOCs) can lead to the underestimation of the yield of SOA (Matsunaga and Ziemann, 2010;Loza et al, 2010;Zhang et al, 2014;Yeh and Ziemann, 2015;Ye et al, 2016;Palm et al, 2016;Krechmer et al, 2016;La et al, 2016;Nah et al, 2017). Since SCI-derived oligomers are the major products of SOA from isoprene-NO 2 irradiations, a question arises about which process is dominant for the reduction of SOA production under humid condition, wall loss of SCI related oligomers (in gas phase), or the reaction between SCI and H 2 O.…”
Section: Other Base Units Of Oligomersmentioning
confidence: 99%